Service quality & customer satisfaction of Singapore public transport. - Lee, Jane Wai Leng. (2008)
This research seeks to examine the level of customer satisfaction in the public transport sector. It provides a guide for the public transport providers to know which are the factors that may be lacking in quality service. For the purpose of this research, we based our analysis on three mode of public transport. They are buses, mass rapid transit (MRT) and taxis. Light Rail Transit (LRT) though is part of the public transport, is not included in this research.